2024
DOI: 10.1017/s1368980023002975
|View full text |Cite
|
Sign up to set email alerts
|

The environmental impact of beef and ultra-processed food consumption in Brazil

Gabriela Lopes da Cruz,
Maria Laura da Costa Louzada,
Jacqueline Tereza da Silva
et al.

Abstract: Objective: This study evaluated the independent and combined environmental impacts of the consumption of beef and ultra-processed foods in Brazil. Design: Cross-sectional study. Setting: Brazil. Participants: We used food purchases data from a national household budget survey conducted between July 2017 and July 2018, representing all Brazilian households. Food purchases were converted into energy, carbon footprints, and water footprints. Multiple line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Adhering to these dietary recommendations would increase overall diet expenditure by 14 to 24%, mainly by promoting higher fruit and vegetable consumption [ 32 ]. Another study with 2017/2018 data found that reducing beef and UPF purchases combined could lead to a 21.1% reduction of the CF and a 20.0% reduction in the WF [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhering to these dietary recommendations would increase overall diet expenditure by 14 to 24%, mainly by promoting higher fruit and vegetable consumption [ 32 ]. Another study with 2017/2018 data found that reducing beef and UPF purchases combined could lead to a 21.1% reduction of the CF and a 20.0% reduction in the WF [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it is imperative to recognize that while BDG and EAT-Lancet diets have reduced environmental impacts, widespread adoption may require targeted policy interventions, educational initiatives, and infrastructural support, reflecting the need for cultural shifts in dietary habits. Especially when we consider the current diet of the Brazilian population, with low consumption of fruits and vegetables, moderate consumption of red meat and dairy and ultra-processed products [ 33 ]. Furthermore, Brazil has seen a progressive increase in UPF and animal protein consumption over time [ 16 ].…”
Section: Discussionmentioning
confidence: 99%